Muslim Cultural Practices in Nepal - Yasmin, Chompa Mousumi (Patan Pragya, 2020)
The purpose of this study is to analyze the cultural practice of Muslims in Nepal. Culture is a shared beliefs, arts, attitudes, values, and socially transmitted behavior patterns of a group or organization. Muslim culture generally includes all the practices which have developed around the religion of Islam, Muslims are rich in culture like other religions in Nepal and they developed a stronger identification with the Nepali state. This paper is based on both primary and secondary data sources followed descriptive method under qualitative approaches.